Synergetic toughening mechanism of spherical α-La phases and micron-sized AlLa3 intermetallic in La-based bulk metallic glass composite. (October 2021) - Zhang, Zibo; Kong, Jian; Liu, Xiangkui; Song, Xinxiang; Dong, Kewei
Abstract: A La74 Al14 Cu6 Ni6 bulk metallic glass matrix composite (BMGMC) with in situ spherical α-La phases and micron-sized AlLa3 intermetallic compounds is prepared by adjusting the processing parameters and presents a good combination of high strength and plasticity. Compared with conventional single α-La dendrite-reinforced La74 Al14 Cu6 Ni6 BMGMCs that have a low fracture strength and plasticity, the obtained composite shows a significant plastic strain of 17% and a high fracture strength of 566 MPa. The results show that the formation of ductile bulky spherical α-La phases and hard AlLa3 intermetallic compounds can effectively hinder the rapid propagation of single shear band, and the synergistic effect of the two phases accounts for the significant increase in plasticity. Furthermore, in situ formed AlLa3 intermetallic compounds with a hardness of 238 HV, which has strong interaction with multiple shear bands, dramatically improve the fracture strength of the composite. Graphical abstract: Image 1 Highlights: Synergistic toughening can effectively improve the mechanical properties of BMGCs. 2.In situ formed AlLa3 intermetallic compounds has strong interaction with multiple shear bands. Composite shows a significant plastic strain of 17% and a high fracture strength of 566 MPa.